2008
DOI: 10.1136/bjo.2008.139725
|View full text |Cite
|
Sign up to set email alerts
|

Cataract in rural Myanmar: prevalence and risk factors from the Meiktila Eye Study

Abstract: The prevalence of cataract in rural Myanmar is similar to that in other developing Asian regions. Cataracts are strongly associated with increasing age, and are more common in those with lower education and lower body mass index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 24 publications
7
47
2
Order By: Relevance
“…Comparison between different studies is inherently difficult for a variety of reasons, and the use of standardized LOCS III classifications is probably the most accurate method. [5][6][7][8][9][10][11] Studies that used different classification systems reported significantly lower prevalence of cataract in Australia (22%) 12,13 and the United States (∼17.5%) 14,15 The prevalence of cataract surgery in this population is very similar to that found in the Meiktila Eye Study (3.9%), 5 but considerably lower than that of Southern India (9.4%). 9 Nuclear cataract is usually the most prevalent of the subtypes, followed closely by cortical cataract, with posterior subcapsular being the least common.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Comparison between different studies is inherently difficult for a variety of reasons, and the use of standardized LOCS III classifications is probably the most accurate method. [5][6][7][8][9][10][11] Studies that used different classification systems reported significantly lower prevalence of cataract in Australia (22%) 12,13 and the United States (∼17.5%) 14,15 The prevalence of cataract surgery in this population is very similar to that found in the Meiktila Eye Study (3.9%), 5 but considerably lower than that of Southern India (9.4%). 9 Nuclear cataract is usually the most prevalent of the subtypes, followed closely by cortical cataract, with posterior subcapsular being the least common.…”
Section: Discussionsupporting
confidence: 71%
“…11,15,20,21 The point prevalence of smoking in this population (over 40 years of age) was 16%, which is lower than many other Asian populations and that of the United States. 5,17,22 Evidence for an association between smoking and cataract (particularly nuclear) continues to grow; the lack of an association in our study may relate to our failure to quantify usage. 23,24 High BMI has previously been linked to cortical cataract, particularly in developed nations.…”
Section: Risk Factors For Cataractcontrasting
confidence: 59%
“…22 This contrasts with surveys in India, 6,23,24 Australia, 25 Taiwan, 26 Finland, 27 China, 28 and Myanmar where NO predominated. 29 More population-based data on the morphological types of opacities are required from Africa to explore reasons for the differences between regions. One explanation for the predominance of CO in our study is that Nigeria lies near the equator, with high sunlight intensity particularly in northern areas, as ultraviolet light is an important risk factor for CO. 8 Another reason may be because cigarette smoking, a risk factor for NO, is uncommon in Africa, including Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is generally believed to accelerate ARC [1,2,3]. Although few evidence support the protective role of obesity against the cataract formation process [25,26], several prospective observational studies have confirmed a positive longitudinal association between obesity and different subtypes of cataract [3]. …”
Section: Discussionmentioning
confidence: 97%
“…Determining the true nature of this correlation is particularly of interest largely due to the controversial role of obesity in ARC; so far that obesity has been proposed as a protective prognostic factor against the formation of ARC in several studies [25,26]. Ideally, the conglomerate of risk factors potentially confounding the association between crystalline lens density and obesity, namely diabetes, nutrition, smoking, and sun exposure [26], should be carefully scrutinized in future related research.…”
Section: Discussionmentioning
confidence: 99%